2016
DOI: 10.1097/jtn.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide Collaboration: Ohio Level III Trauma Centers' Approach to the Development of a Benchmarking System

Abstract: The American College of Surgeons Committee on Trauma revised the Resources for Optimal Care of the Injured Patient to include the criteria for trauma centers to participate in a risk-adjusted benchmarking system. Trauma Quality Improvement Program is currently the risk-adjusted benchmarking program sponsored by the American College of Surgeons, which will be required of all trauma centers to participate in early 2017. Prior to this, there were no risk-adjusted programs for Level III verified trauma centers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The former authors admitted that the success of their program was partially due to marketing (Byrnes et al, 2010), which is unsurprising considering that anecdotally, many outreach programs across the United States have been described as marketing schemes. Lang et al reported on a successful statewide outreach committee made up of trauma program managers, coordinators, and other program leaders, which came together and discussed benchmarking and PI of rural centers up to six times a year (Lang et al, 2016). The program's success described by Lang and colleagues was largely determined by the leadership and consistency of the committee, which created a good working relationship with trauma medical directors across rural centers to improve trauma care ultimately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former authors admitted that the success of their program was partially due to marketing (Byrnes et al, 2010), which is unsurprising considering that anecdotally, many outreach programs across the United States have been described as marketing schemes. Lang et al reported on a successful statewide outreach committee made up of trauma program managers, coordinators, and other program leaders, which came together and discussed benchmarking and PI of rural centers up to six times a year (Lang et al, 2016). The program's success described by Lang and colleagues was largely determined by the leadership and consistency of the committee, which created a good working relationship with trauma medical directors across rural centers to improve trauma care ultimately.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, few studies have been published on trauma outreach programs, particularly in rural settings. Current outreach literature is primarily focused on performance improvement (PI) (Bradley et al, 2017; Byrnes et al, 2010; Lang et al, 2016), rural trauma development courses (Dennis et al, 2016; Gutenstein et al, 2019; Kappel et al, 2011), and other continuing medical education (Sidwell & Matar, 2017) designed to bolster education for rural trauma centers. Although all parts are necessary to run an outreach program, many previously mentioned studies are not current.…”
Section: Introductionmentioning
confidence: 99%
“…In a single state study in Ohio, one such study reported on the development of a benchmarking program for level III centers. This effort included structural measures (emergency department volume, rurality), process measures (average surgeon response time, % of orthopedic fractures managed operatively within 24 hours), and outcome measures (raw mortality) (11). Another single-state study from Colorado described the development of performance improvement filters relevant to level III and IV trauma centers, including such process measures as adherence to trauma team activation criteria, response time for trauma team leaders, and time to intubation for patients with Glasgow Coma Scores<9 (12).…”
Section: Discussionmentioning
confidence: 99%